2021
DOI: 10.7494/geom.2021.15.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Land Surface Temperature Before, During and After the Covid‑19 Lockdown Using Landsat Imagery: A Case Study of Casablanca City, Morocco

Abstract: Land Surface Temperature (LST) is an important variable within global climate change. With the appearance of remote sensing techniques and advanced  GIS software, it is now possible to estimate LST. In this study, the effect of lockdown during COVID-19 on the LST was assessed using Landsat 8 Imagery.  LST dynamic was investigated for three different periods: Before, during  and after the COVID-19 lockdown. The study was conducted in Casablanca  City. The results showed that during the emergence of COVID-19 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…For example, changes in the anthropogenic heat release related to road traffic emissions and energy consumption for heating and cooling buildings modified the airand land surface temperatures (LST) of cities [7][8][9]. Numerous studies investigated the LST changes during the first lockdown [9][10][11][12] and observed a general decline in mean LST compared with the previous years. For instance, Liu et al [9] found that during the lockdown, the surface urban heat island intensity (SUHII) in China decreased by 0.25 K during the day and 0.23 K at night, and the canopy-layer UHII by 0.42 K during the day and 0.39 K at night, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, changes in the anthropogenic heat release related to road traffic emissions and energy consumption for heating and cooling buildings modified the airand land surface temperatures (LST) of cities [7][8][9]. Numerous studies investigated the LST changes during the first lockdown [9][10][11][12] and observed a general decline in mean LST compared with the previous years. For instance, Liu et al [9] found that during the lockdown, the surface urban heat island intensity (SUHII) in China decreased by 0.25 K during the day and 0.23 K at night, and the canopy-layer UHII by 0.42 K during the day and 0.39 K at night, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Palermo and Cagliari (cities in southern Italy) were selected as test sites because it was possible to acquire Landsat 8 and Landsat 9 images on the same day and within a suitable time frame. Such open medium-resolution satellite data is preferable for environmental monitoring and climate change studies, as it allows us to estimate many bio-geophysical variables as well as their spatial and temporal variabilities [10,16,[57][58][59][60][61][62][63][64][65]. Measuring and monitoring albedo levels is crucial for addressing issues such as UHI and drought, which are caused by changes in the energy fluxes between land surfaces and the atmosphere [1,3,5,[10][11]18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that the COVID-19 closure has decreased surface temperatures. Our work evaluated LST variations, just like earlier studies (Arrofiqoh & Setyaningrum, 2021 ; Ghosh et al, 2020 ; Marvi et al, 2021 ; Taoufik et al, 2021 ; Teufel et al, 2021 ) that noted urban temperature changes as a result of COVID-19. We used 14 LANDSAT 8 OLI/TIRS satellite images from 2016 and 2022 to calculate the LST values.…”
Section: Discussionmentioning
confidence: 99%
“…NO 2 , AOD, and SUHII levels were found to be lower (Alqasemi et al, 2021 ). Taoufik et al, 2021 employed Landsat 8 OLI/TIRS long-term data from 2016 to 2020. When the average values were examined, it was discovered that the LST averages at Morocco dropped during the COVID-19 period (Taoufik et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation